A Meta-Analysis of Randomized Controlled Trials on Antiplatelet Agents Versus Placebo/Control for Treating Peripheral Artery Disease. Issue 31 (August 2015) - Qian, Jun; Yang, Xiao Hong; Anastasios, Lymperopoulos.
<x xml:space="preserve">Abstract</x> Abstract Effect of aspirin (antiplatelet agents) in patients with peripheral artery disease (PAD) was still controversial. Varying studies reported varying results. Therefore, we did this meta-analysis to investigate if aspirin could reduce cardiovascular events in patients with PAD. A comprehensive literature search (PubMed, CCTR, Embase, Web of Science, CNKI, CBM-disc, and relevant websites) was conducted from 1990 to September 2014. The key search terms ("aspirin, " "PAD, " "peripheral arterial occlusive diseases, " and "claudication") produced 9 high-quality randomized controlled trials (RCTs) of aspirin versus placebo/control. Mantel–Haenszel random-effects model was used to analysis of the 9 RCTs. The primary outcome was the cardiovascular events. Nine RCTs, composed of 9526 patients (4786 aspirin-treated and 4740 placebo or control-treated patients), were meta-analyzed. The results indicated that compared to placebo/control, aspirin could not significantly reduce the cardiovascular events (OR = 0.81, 95% CI = 0.56–1.15). Moreover, aspirin could not produce better effect on prevention of nonfatal myocardial infarction (OR = 0.98, 95% CI = 0.52–1.84), nonfatal stroke (OR = 0.89, 95% CI = 0.69–1.14), cardiovascular death (OR = 0.97, 95% CI = 0.68–1.38), any death (OR = 1.05, 95% CI = 0.85–1.30), and major bleeding (OR = 1.16, 95% CI = 0.82–1.65) than placebo/control. But aspirin, as monotherapy therapy, did significantly reduce the risk of nonfatal stroke (OR = 0.42, 95% CI = 0.21–0.84). Aspirin, as monotherapy or combination therapy, did not result in a significant decrease in the cardiovascular events. But aspirin, as monotherapy therapy, did significantly reduce the risk of nonfatal stroke. Our conclusion might help clinicians in clinical treating PAD. Future studies are needed to draw firm conclusions about the clinical benefit and risks of aspirin and other antiplatelet agents.